2007
DOI: 10.1111/j.1440-1681.2007.04668.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilatation Induced by Sinomenine Lowers Blood Pressure in Spontaneously Hypertensive Rats

Abstract: 1. Sinomenine is an alkaloid with a wide range of pharmacological actions. In the present study, we investigated the effect of sinomenine on blood pressure and its possible mechanisms of action. 2. Spontaneously hypertensive rats (SHR) and normotensive Wistar-Kyoto (WKY) rats were given intraperitoneal injections of sinomenine. At 30 min, 2.5-10 mg/kg sinomenine decreased systolic blood pressure (SBP) in a dose-dependent manner in SHR, but had no effect on the SBP in WKY rats. 3. The vascular effect of sinomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The intracellular signals linked with the NPR-C receptor have been demonstrated in cardiovascular tissues and cells [11]. Recently, it has been reported that ANP interacts with NPR-C in atria, ventricles, and the aorta to activate Ca 2+ -loaded calmodulin and endothelial nitric oxide synthase (eNOS) through the Gi protein [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular signals linked with the NPR-C receptor have been demonstrated in cardiovascular tissues and cells [11]. Recently, it has been reported that ANP interacts with NPR-C in atria, ventricles, and the aorta to activate Ca 2+ -loaded calmodulin and endothelial nitric oxide synthase (eNOS) through the Gi protein [12].…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the intracellular calcium concentration were detected using the fluorescent probe fura-2 [11]. A7r5 cells were placed in buffered physiological saline solution (PSS) containing 140 mM NaCl, 5.9 mM KCl, 1.2 mM CaCl 2 , 1.4 mM MgCl 2 , 11.5 mM glucose, 1.8 mM Na 2 HPO 4 , and 10 mM Hepes-Tris; next, 5 µM fura-2 was added to this solution; and then, the cells were incubated for 1 h in humidified atmosphere containing 5% CO 2 and 95% air at 37° C. The cells were washed and incubated for further 30 min in PSS.…”
Section: Methodsmentioning
confidence: 99%
“…The changes in the intracellular calcium concentration were detected using the fluorescent probe fura-2 (Lee et al 2007). Min 6 cells were placed in buffered physiological saline solution containing 140 mM NaCl, 5 .…”
Section: Measurement Of Intracellular Calcium Concentrationsmentioning
confidence: 99%
“…Sinomenine, a natural alkaloid, was isolated from the roots of Sinomenium acutum, and a variety of bioactivities have been reported, such as inhibition of the growth of several cancers [14][15][16][17][18], dilation of vascular to lower pressure [19], blocking tissue modeling after chronic cardiac allograft rejection [20], anti-angiogenesis [21] and anti-inflammation [22][23][24]. Due to its anti-inflammatory and antirheumatic effects, sinomenine has been employed clinically for the treatment of RA in China for a long time [25,26].…”
Section: Introductionmentioning
confidence: 99%